Effect of Green Tea and its bioactive compound, (-)- Epigallocatechin-3-Gallate, on Weight Reduction and on Cytochrome P450 / Ng Mei Fong - Ng, Mei Fong (2018)
Obesity is presently considered to be an epidemic, affecting more than 10% of adult population worldwide since the 19th century. However, gene regulations that are involved in obesity are not clearly understood. Green tea (Camelia sinensis) and its main component, (-)-epigallocatechin-3-gallate (EGCG) have been claimed to have anti-obese property. In order to understand the genes that are involved in obesity, changes in gene expression during obesity development in a mouse model was examined. We aimed to understand how green tea extract and EGCG affect gene regulation during obesity development and since they have been claimed to possess anti-obese property, we also aimed to examine gene expression in the mouse during development of obesity. Since green tea is widely consumed, the question arises as to whether it can interact with cytochrome P450 (CYP) enzymes to cause herb-drug interactions. To examine this, the interaction of green tea extracts (methanol extractGTME, water extract-GTWE and hexane extract-GTHE) and of EGCG with human recombinant CYP enzymes CYP3A4, CYP2D6, CYP1A2, CYP2C9 and CYP2C19 were investigated. Results of the animal study showed that high fat diet (HFD) induced weight gain (29.85 ± 2.34%) by 10% higher than the normal group (19.18 ± 1.95%) in 4 weeks. However, in the groups that were treated with green tea extract and EGCG, no obvious increase in weight were observed (5.74 ± 1.69% and 3.34 ± 2.27% respectively). For the study on gene expression, we found that genes that were upregulated or downregulated were related to metabolic syndrome directly or indirectly. A total of 1024 genes were irregulated in HFD suggested that these genes were involved in obesity development. A total of 1892 genes in HFD + GTE and 1817 genes in HFD + EGCG were irregulated in these samples, suggesting that the genes were involved in prevention of obesity. The overall results showed that green tea extract and EGCG are able to prevent obesity in mouse model. In the study on effects of green tea and EGCG iv on CYP enzymes, the order of potency of the green tea extracts and EGCG on CYPs is: EGCG > GTME > GTWE > GTHE. EGCG showed the strongest inhibitory effect on CYP1A2 (Ki: 0.94 μg/mL), CYP2C19 (Ki: 1.26 μg/mL), CYP3A4 (Ki: 3.28 μg/mL) and CYP2C9 (Ki: 6.79 μg/mL). GTME had strongest inhibitory effects on CYP2C19 (Ki: 2.08 μg/mL), CYP3A4 (Ki: 4.94 μg/mL) and CYP1A2 (Ki: 5.00 μg/mL) while GTWE had strongest inhibitory effects on CYP1A2 (Ki: 7.95 μg/mL) and CYP2C19 (Ki: 8.73 μg/mL). The CYP inhibition activities of the GTME and GTWE were suggested to be related to their EGCG content. Extracts with higher content of EGCG appeared to be more potent. Further investigation revealed that EGCG, GTME, GTHE and GTWE inhibited CYP1A2 and CYP2C19 non-competitively, and caused mixed competitive inhibition against CYP3A4. Specifically for CYP2D6, GTME and EGCG exhibited mixed competitive inhibition, while GTWE showed un-competitive inhibition. As for CYP2C9, GTME, GTWE and EGCG showed mixed competitive inhibition while GTHE showed un-competitive inhibition. These findings suggest that green tea extracts and EGCG are likely to contribute to herb-drug interactions when orally coadministered with drugs metabolized by CYP3A4, CYP2D6, CYP1A2, CYP2C9 and CYP2C19.